Evidence for serotonin as a relevant inducer of liver regeneration after liver resection in humans. Issue 1 (July 2014) - Starlinger, Patrick; Assinger, Alice; Haegele, Stefanie; Wanek, David; Zikeli, Silvia; Schauer, Dominic; Birner, Peter; Fleischmann, Edith; Gruenberger, Birgit; Brostjan, Christine; Gruenberger, Thomas
<x xml:space="preserve">Abstract</x> Liver regeneration (LR) involves a complex interplay of growth factors and antagonists. In this context, platelet‐derived serotonin (5‐HT) has been identified as a critical inducer of LR in mice. Clinical evidence for a role of 5‐HT in LR in humans is lacking. Accordingly, serum and plasma 5‐HT was monitored perioperatively in 60 patients undergoing liver resection, of which 35 served as exploration and 25 as validation sets. Intraplatelet (IP) levels of 5‐HT were calculated by subtraction of plasma 5‐HT from serum values. Serum markers of liver function were used to evaluate LR and liver dysfunction (LD). In the exploration setting, IP 5‐HT levels significantly decreased after liver resection (P < 0.001) and gradually recovered during the first week. IP 5‐HT measured before surgery specifically predicted LD in the subsequent 7 days (area under the curve: 0.721; P = 0.029). Patients suffering from postoperative LD and morbidity were found to have reduced IP 5‐HT levels during the entire perioperative period. Furthermore, we validated that reduced preoperative IP 5‐HT (<73 ng/mL) was associated with an increased incidence of postoperative LD and morbidity (P =0.045 and P = 0.021) and were able to demonstrate that IP 5‐HT levels were an independent predictor of poor clinical outcome. Conclusions: These findings provide evidence that IP 5‐HT correlates with LR in humans: Patients with low IP 5‐HT before liver resection suffered from delayed hepatic regeneration. Therefore, IP 5‐HT levels may prove a helpful clinical marker to predict postoperative LD and clinical outcome before hepatic resection and initiate suitable interventions. (Hepatology 2014;60:257‐266)